Developing the Dead : Mediumship and Selfhood in Cuban Espiritismo - Espirito Santo, Diana (Book collections on Project MUSE., 2015)
This book is the first sustained, deep ethnographic study of Espiritismo (Spiritism) in Cuba. In it, Espirito Santo examines in-depth the daily rhythms of how individual practitioners' experiences and conceptions of selfhood are shaped.